PERFORMANCE ANALYSIS TUGU KETUPAT KANDANGAN II ROUNDABOUT - Nurin, Majdina; Arsyad, Muhammad (Universitas Lambung Mangkurat, 2023)
A roundabout is a type of intersection in which there is a circular island in the middle where the movement of the intersection is replaced by a weaving, distracting vehicles from straight traffic and slowing it down. Roundabouts have the advantage of slowing all passing vehicles and warning of the danger of collisions with other vehicles. There is a transition where special vehicles must use the by-pass road, resulting in traffic on Jl. Al-Falah – Brigjen H.M. Yusi increased . Based on these conditions, an analysis of the performance of the Tugu Ketupat Kandangan II roundabout was carried out to determine the performance of the roundabout in current and future conditions. In this study, roundabout geometric data and a traffic volume survey were collected which was carried out 1 day from 06:00 - 20:00 WITA. In addition, the analysis was carried out using the calculation method of the Manual Kapasitas Jalan, 1997 to determine the degree of saturation, queuing opportunities, delays, and capacity values found at the Tugu Ketupat Kandangan II roundabout. The current roundabout performance analysis reveals that the roundabout saturation value is 0.653. The capacity values for AB = 4310 pcu/hour, BC = 3781 pcu/hour, CA = 3440 pcu/hour. The value of the degree of saturation for AB = 0.471, BC = 0.653, and CA = 0.495. The average delay value is 4 sec /pcu. The queue probability value is 17%. For the next year's roundabout performance, the specified parameters are not fulfilled and the existing traffic flow can not be served. The research shows that several alternative solutions are needed and evaluated every few years to support the smooth, safe, and orderly traffic at the Tugu Ketupat Kandangan II roundabout. Keywords: Degree of saturation, queue probability, delay, roundabout performance analysis